Decision Support System for Selecting Tourist Object in Surabaya City Using Simple Additive Weighting Based on Android - Putri Agustin Merditawati; M Mahaputra Hidayat (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
In this Final Project will be discussed regarding the implementation of the Attraction Decision Support System in Surabaya using Simple Additive Weighting. The problem to be taken is to get the best results from 50 attractions in the city of Surabaya based on the user's location by using an Android-based operating system, to make it easier for users to access this application. To obtain the value of distance criteria, this application uses the Haversine formula. The results of the study of the decision support system application for the selection of attractions in the city of Surabaya using the Simple Additive Weighting method is the highest value obtained from attractions based on the user's location with weights for each criterion especially the distance criteria which has a weight of 0.3.